Exploring tribological properties in the design and manufacturing of metal matrix composites: an investigation into the AL6061-SiC-fly ASH alloy fabricated via stir casting process - Kumar Murmu, Sagar; Chattopadhayaya, Somnath; Cep, Robert; Kumar, Ajay; Kumar, Ashwini; Kumar Mahato, Shambhu; Kumar, Amit; Ranjan Sethy, Priya; Logesh, K. (Frontiers in Materials, 2024)
This study investigates a novel methodology to intricately craft a HAMMC and thoroughly examine its multifaceted mechanical and tribological characteristics. By combining silicon carbide (SiC) and fly ash as reinforcements, a unique identity is bestowed upon this hybrid composite, enhancing its structural integrity and functional attributes. Stir casting is the chosen methodology for fabricating this composite, favored for its economic viability and suitability for large-scale manufacturing. In this research, the emphasis is on developing a cost-effective composite that not only meets stringent economic considerations but also exhibits improved material properties. Within the realm of hybrid metal matrix composites, the well-regarded Al6061 takes on the role of the matrix material, while the synergistic inclusion of fly ash and SiC serves as reinforcing constituents. Three specimens with compostion 90% Al6061 + 5% SiC + 5% Fly ash, 90% Al6061 + 10% SiC + 6% Fly ash and 90% Al6061 + 15% SiC + 7% Fly ash were fabricated. To unravel the intricacies of the fabricated Al6061 metal matrix composite, comprehensive tests are employed. These tests, including the Pin-on Disc test, Scratch test, Rockwell Hardness test, and Charpy Impact test, collectively work to unveil the nuanced tribological and mechanical behaviors encapsulated within this innovative alloy.The results indicated significant improvement in wear resistance in specimen comprising 78% Al6061 + 15% SiC + 7% Fly Ash and volumetric loss found to have 0.96 grams. Superior hardness characteristics and enhanced abrasion resistance found in 78% Al6061 + 15% SiC + 7% Fly Ash than other two specimens. The highest impact strength exhibited in 90% Al 6061 + 5% SiC + 5% Fly ash specimen.